2021
DOI: 10.3390/jcm10102175
|View full text |Cite
|
Sign up to set email alerts
|

Why do We Use the Concepts of Adult Anesthesia Pharmacology in Developing Brains? Will It Have an Impact on Outcomes? Challenges in Neuromonitoring and Pharmacology in Pediatric Anesthesia

Abstract: Background: Pediatric sedation and anesthesia techniques have plenty of difficulties and challenges. Data on the pharmacologic, electroencephalographic, and neurologic response to anesthesia at different brain development times are only partially known. New data in neuroscience, pharmacology, and intraoperative neuromonitoring will impact changing concepts and clinical practice. In this article, we develop a conversation to guide the debate and search for a view more attuned to the updated knowledge in neurode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…They observed that activating α2-AdR in nodal papillae nuclei to inhibit the ventrolateral preoptic area (VLPO) subsequently inhibited the tuberomammillary nucleus (TMN) via GABA release, similar to selective injections of anesthetics or GABA agonists into the nucleus. However, dexmedetomidine does not significantly alter cortical EEG frequencies, and subcortical function remains connected in anesthetized mice, maintaining interaction between the cortex and thalamus [32,109]. Notably, dexmedetomidine does not reliably induce unconsciousness; its primary use is in sedation, particularly beneficial in "awake craniotomy" where patient communication is necessary [108].…”
Section: Study On Neural Circuit Involved In Different Anestheticsmentioning
confidence: 99%
“…They observed that activating α2-AdR in nodal papillae nuclei to inhibit the ventrolateral preoptic area (VLPO) subsequently inhibited the tuberomammillary nucleus (TMN) via GABA release, similar to selective injections of anesthetics or GABA agonists into the nucleus. However, dexmedetomidine does not significantly alter cortical EEG frequencies, and subcortical function remains connected in anesthetized mice, maintaining interaction between the cortex and thalamus [32,109]. Notably, dexmedetomidine does not reliably induce unconsciousness; its primary use is in sedation, particularly beneficial in "awake craniotomy" where patient communication is necessary [108].…”
Section: Study On Neural Circuit Involved In Different Anestheticsmentioning
confidence: 99%
“…Early Development Instrument (EDI), composed of 104 items to assess physical health and well-being, language and cognitive skills, social competence, emotional development, and communication ability and general knowledge [17]; Over the years, significant improvements in terms of monitoring, medications and anesthesiological techniques have been obtained in the field of pediatric anesthesia, thus leading to improvements in recovery after surgical interventions and overall survival following early surgeries [23]. A crucial point has been the recent conceptualization of pediatric anesthesia, which should be approached differently compared to the one for adults, especially from a pharmacological point of view [24]. Nonetheless, despite the controversy surrounding the FDA alert, there is still no international consensus on the effects of early exposure to anesthetic drugs.…”
mentioning
confidence: 99%